2020
DOI: 10.1002/ieam.4345
|View full text |Cite
|
Sign up to set email alerts
|

Residue Levels of Pesticides on Fruits for Use in Wildlife Risk Assessments

Abstract: The guidance document on risk assessment for birds and mammals (GD) provides generic residue values of pesticides on potential diet items for use in wildlife risk assessments. For most diet items, these values are based on a large number of residue studies. However, the default residues per unit dose (RUD; standardized for application of 1 kg substance per hectare) values for fruits were taken from a few literature trials of unclear relevance for regulatory purposes. These trials were conducted according to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Also, heavy use of agro‐chemicals, together with landscape homogenisation, may reduce the availability of alternative foods (Bergmeier & Strid, 2014; Cárdenas et al., 2006; Rey, 2011; Ruano et al., 2004; Solomou & Sfougaris, 2011), which may be problematic in late winter when olive availability is low. Finally, olives may be contaminated with pesticide residues (Cabras et al., 1997), with poorly known but potentially serious consequences for birds (Schabacker et al., 2020). Overall, our results are encouraging regarding the ability of intensive olive farming to sustain frugivorous birds, but we recommend that exposure to risks should be reduced by stopping night harvest (Silva & Mata, 2019), increasing heterogeneity at local (woody hedges, herbaceous cover) and landscape (semi‐natural habitats and diverse land uses, including different olive orchard types) scales to promote alternative food sources (Assandri et al., 2017; Bouvier et al., 2020; Castro‐Caro et al., 2015; Rey et al., 2019) and reducing agro‐chemical use to avoid negative effects on birds and their foods (Rey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Also, heavy use of agro‐chemicals, together with landscape homogenisation, may reduce the availability of alternative foods (Bergmeier & Strid, 2014; Cárdenas et al., 2006; Rey, 2011; Ruano et al., 2004; Solomou & Sfougaris, 2011), which may be problematic in late winter when olive availability is low. Finally, olives may be contaminated with pesticide residues (Cabras et al., 1997), with poorly known but potentially serious consequences for birds (Schabacker et al., 2020). Overall, our results are encouraging regarding the ability of intensive olive farming to sustain frugivorous birds, but we recommend that exposure to risks should be reduced by stopping night harvest (Silva & Mata, 2019), increasing heterogeneity at local (woody hedges, herbaceous cover) and landscape (semi‐natural habitats and diverse land uses, including different olive orchard types) scales to promote alternative food sources (Assandri et al., 2017; Bouvier et al., 2020; Castro‐Caro et al., 2015; Rey et al., 2019) and reducing agro‐chemical use to avoid negative effects on birds and their foods (Rey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Different berries, pome, and stone fruits exhibit a variety of shapes, sizes, and surfaces. Particularly, fruit size, volume–surface area relationship, and details of the skin structure likely influence the residue levels [ 37 ]. In previous studies, it was found that the residues of boscalid and pyraclostrobin in apples were at levels of 0.049 ± 0.007 mg/kg and 0.032 ± 0.003 mg/kg, respectively, which were similar to our results [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The residual concentrations of fenpyroximate in citrus flesh were lower than those in entire fruits because droplets of pesticides wholly adhered to the surface of the citrus peel after application. The total residues of fenpyroximate in whole fruit and citrus flesh were all derived from fenpyroximate because the chemical configuration of fenpyroximate in plants gives it an advantage compared to Z-fenpyroximate [25].…”
Section: Terminal Residuesmentioning
confidence: 99%